(untitled) (Transport systems and technologies, 2020)
Among the main causes of human operator errors are the following: unsatisfactory training or low level of qualification; non-compliance with the prescribed operating procedures; unsatisfactory working conditions associated with such negative phenomena as excessive noise, vibration, temperature fluctuations in the driver’s cab (especially on locomotives); lack of attractive incentives to achieve the optimal level of quality of work. The choice of the criterion of optimal control can be ambiguous. The source of complexity is the inconsistency of goals. If you want to optimize one of the parameters in compliance with the restrictive requirements for other parameters, then a partial criterion is formed. In the presence of several optimality criteria, the additive criterion is chosen when the absolute values of the criteria are significant for the selected parameter vector. If a significant role is played by changes in absolute values of partial criteria in the variation of the vector of variables, then apply the multiplicative criterion of optimality. If the task is to achieve equality of normalized values of conflicting partial criteria, then the optimal design is performed by the minimum criterion.